Theoretical Analysis and Experimental Study of Gravity Recirculation Refrigeration System - Ruan Jianwen; Zhang Cheng; Li Min; Ye Biao (Zhileng xuebao)
The gravity recirculation refrigeration system has two significant advantages compared with the ordinary direct-expansion refrigeration system. The lower the evaporation temperature, the clearer the efficiency advantage, and the lower temperature obtained in the chamber. In this study, the pressure enthalpy diagram of a gravity recirculation system is redesigned based on the principle of a gravity recirculation system, and the thermodynamic cycle of a gravity recirculation system is divided into two cycles for analysis. By analyzing the flow resistance in the refrigerant flow process, the variation trend of the pressure in each part of the system is obtained. The experimental results show that the pressure at each state point is identical to the theoretical analysis results. The coefficient of performance (COP) of the gravity recirculation refrigeration system can be improved by up to 19% at different evaporation temperatures compared with the experimental results of the ordinary direct-expansion refrigeration system, and the COP reaches 1.07 at ?30 °C.